Kommunikative Rationalität für Statistical Literacy: Ein Framework zur Analyse der Kommunikation von Lernenden über datenbasierte Argumentationen (mathematica didactica, 2025)
Whereas data literacy focuses on an individual’s ability to utilize data, statistical literacy focuses on two interlocutor’s ability to interpret and communicate about data-based arguments. The communicative component of statistical literacy, however, remains underdeveloped in research discourse. This contribution illustrates a framework for the communicative component by adapting Habermas’ rationality constructs. The results of an empirical study show that the framework allows deep insights into students’ statistical literacy. This also allows a clearer specification of the relation between data literacy and statistical literacy.